Resposta da Vegetação Campos de Altitude às Mudanças Climáticas na Faixa Altitudinal Acima de 400 Metros na Serra do Amolar e Morraria do Urucum, Pantanal Brasileiro - Dhonatan Diego Pessi; Normandes Matos da Silva; Camila Leonardo Mioto; Alfredo Marcelo Grigio; Francisco das Chagas Oliveira; Vinicius de Oliveira Ribeiro; Fábio Veríssimo Gonçalves; Marco Antonio Diodato; Roberto Macedo Gamarra; Felipe Siqueira Pacheco; Antonio Conceição Paranhos Filho (Terr@ Plural)
This study aims to examine the driving effects of climate change on the spatial distribution of altitude grassland vegetation along an altitudinal range above 400 m in Serra do Amolar and Morraria do Urucum, both inserted in the Pantanal wetlands located in the State of Mato Grosso do Sul, Brazil. Data variables from Google Earth Engine was obtained to the 1982-2022 period for climate data and from 1985 to 2022 for NDVI (Normalized Difference Vegetation Index) data. The data were processed and analyzed using the R software, in which the analysis metrics were applied on the raster data to identify spatial variation of the NDVI means and statistical methods such as Pearson’s correlation and simple linear regression were applied to identify the strength of the relationship between climate variables and the NDVI. The results showed that there was an increasing trend in temperature, NDVI and precipitation over the 37 years analyzed. The climatic variables were statistically relevant in the tests of the relationship between the NDVI and the variables of temperature, precipitation and spatial change in vegetation cover. The study thus revealed the merit of this analysis with a technical approach to assess the contribution of climate change versus alteration in vegetation dynamics in mountainous ecosystems.